Optimalkan Keamanan Website Implementasi Penilaian Keamanan Website Komprehensif Pada Situs SMA Negeri 1 Surade: Evaluasi dan Pemeliharaan Keamanan Website: Tantangan dan Solusi - Salman Alhidamkara; Ivana Lucia Kharisma; Kamdan (Computer Science and Information Technology, 2023)
In the era of rapid development in media information, the utilization of websites as sources of information has gained widespread significance across various sectors. However, with the increasing use of websites, attention to security aspects has become crucial. The urgency to analyze its vulnerabilities has proven essential in efforts to detect potential threats in the future and ensure the continuity of confidentiality, consistency, accuracy, data validity, and information availability—known as the CIA Principles (Confidentiality, Integrity, Availability)—forming the fundamental basis for safeguarding information security. The website of Public High School 1 Surade presents both general and sensitive data related to school and student information. The findings of this research are expected to make a significant contribution in raising awareness about website security, offering valuable guidance to educational institutions and the government. The aim is to strengthen the security of their websites, with the hope of reducing potential cyber threats in Indonesia. This research is anticipated to serve as a foundation for more effective preventive measures and stricter information security policies.